2009
DOI: 10.1111/j.1463-1326.2009.01039.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and linear exposure of AFRESA™ compared with the subcutaneous injection of regular human insulin

Abstract: TI is an inhaled insulin with a more rapid absorption and a more rapid elimination than subcutaneously administered RHI, resulting in a quick onset and short duration of action. Insulin exposure following TI administration was found to be linear over the dose range of 25-100 U.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
64
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(70 citation statements)
references
References 8 publications
5
64
0
1
Order By: Relevance
“…The time-action profile of TI is characterized by a very rapid onset of action and a very short duration of action. [31][32][33] The uptake of TI is significantly faster than RHI, with a reported T max of 12 to 17 min for doses of 25 to 100 U of TI (bioavailability relative to SC insulin was 21-25%) and glucose infusion rate (GIR) T max 42-58 versus 174 min for RHI. 34 In a phase 3 study comparing glargine plus TI inhaled preprandially with biphasic (biaspart) SC injections twice daily, changes in HbA1c with TI were noninferior/equivalent, despite the much faster PKs.…”
Section: Inhalation Of Rapidly Absorbed Insulinmentioning
confidence: 99%
“…The time-action profile of TI is characterized by a very rapid onset of action and a very short duration of action. [31][32][33] The uptake of TI is significantly faster than RHI, with a reported T max of 12 to 17 min for doses of 25 to 100 U of TI (bioavailability relative to SC insulin was 21-25%) and glucose infusion rate (GIR) T max 42-58 versus 174 min for RHI. 34 In a phase 3 study comparing glargine plus TI inhaled preprandially with biphasic (biaspart) SC injections twice daily, changes in HbA1c with TI were noninferior/equivalent, despite the much faster PKs.…”
Section: Inhalation Of Rapidly Absorbed Insulinmentioning
confidence: 99%
“…15 Ultrafast insulin products are being developed that provide an even more rapid PK profile compared with current rapid prandial insulin products. 10,16,17 For example, an inhaled, dry powder insulin formulation has been developed that has a substantially faster time to peak plasma concentration (t max ) vs regular human insulin (12 to 17 minutes vs 2 hours postdose, respectively) and a more rapid return to baseline insulin concentrations (42 to 50 minutes) vs regular insulin (284 minutes). 17 The overall strategy of these ultrafast insulin products is to better mimic the normal physiologic response to insulin that occurs in healthy individuals to provide important clinical benefits in the control of postprandial hyperglycemic excursions.…”
Section: Introductionmentioning
confidence: 99%
“…10,16,17 For example, an inhaled, dry powder insulin formulation has been developed that has a substantially faster time to peak plasma concentration (t max ) vs regular human insulin (12 to 17 minutes vs 2 hours postdose, respectively) and a more rapid return to baseline insulin concentrations (42 to 50 minutes) vs regular insulin (284 minutes). 17 The overall strategy of these ultrafast insulin products is to better mimic the normal physiologic response to insulin that occurs in healthy individuals to provide important clinical benefits in the control of postprandial hyperglycemic excursions. Some of these ultrafast insulin formulations have demonstrated additional benefits, such as reduced weight gain and fewer hypoglycemic events, compared with regular human insulin 18 or rapid-acting insulin analogs.…”
Section: Introductionmentioning
confidence: 99%
“…These characteristics had basically been confirmed by a meal-test study in patients with type 2 diabetes, which demonstrated a more rapid absorption and higher peak insulin levels as well as markedly improved postprandial glycemic control with the inhaled insulin compared with subcutaneous regular human insulin (110). A linear systemic insulin uptake profile was noted in studies employing healthy volunteers inhaling three doses of insulin (106)(107)(108). In addition, the within-subject variability of insulin exposure following inhalation of Technosphere™ insulin was lower compared to regular insulin (109).…”
Section: Current Ultrafast Insulin Formulationsmentioning
confidence: 89%
“…At the neutral pH environment of the lungs, the microparticles dissolve rapidly and insulin is absorbed across the pulmonary epithelium into the systemic circulation, while the carrier is cleared unmetabolized (104,106). The pharmacokinetic clamp studies performed in healthy volunteers and patients with type 2 diabetes revealed a very rapid systemic insulin uptake (time to maximal insulin concentration around 15 minutes) with a subsequent fast onset of action (time to maximal metabolic effect of about 40-80 minutes) and a short duration of action (106)(107)(108)(109). These characteristics had basically been confirmed by a meal-test study in patients with type 2 diabetes, which demonstrated a more rapid absorption and higher peak insulin levels as well as markedly improved postprandial glycemic control with the inhaled insulin compared with subcutaneous regular human insulin (110).…”
Section: Current Ultrafast Insulin Formulationsmentioning
confidence: 99%